(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1964)
At the Anniversary meeting the President made several announcements to the Fellows and then a list of newly elected Fellows was presented, as was a list of deceased Fellows. The Annual Report was then delivered, covering topics such as Fellowship, Meetings, Administration, and publications. The Treasurer then presented the Society’s accounts for 1961-62.